2008
DOI: 10.1007/s11596-008-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the expression of RASSF1A protein and promoter hypermethylation of RASSF1A gene in bladder tumor

Abstract: To investigate the relationship between the expression of RASSF1A protein and promoter hypermethylation of RASSF1A gene, RASSF1A protein expression was measured by Western blotting in 10 specimens of normal bladder tissues and 23 specimens of bladder transitional cell carcinoma (BTCC). The promoter methylation in BTCC and normal bladder tissues was detected by methylation-specific PCR (MSP). The results showed that the expression level of RASSF1A protein was significantly lower in BTCC tissues than that in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The decreased levels of RASSF1A in ccRCC described in the study present a novel observation. The finding of the relation between low levels of RASSF1A in ccRCC samples and progression of cancer (TNM and Fuhrman's grading) support the role of RASSF1A as a tumor suppressor gene also in ccRCC, similarly to other types of cancer ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 56%
“…The decreased levels of RASSF1A in ccRCC described in the study present a novel observation. The finding of the relation between low levels of RASSF1A in ccRCC samples and progression of cancer (TNM and Fuhrman's grading) support the role of RASSF1A as a tumor suppressor gene also in ccRCC, similarly to other types of cancer ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 56%
“…It has been suggested that RASSF1A methylation is one of the most common aberrations so far identified in human cancers and that the loss of the functional protein may promote the development of many human tumors. Hypermethylation of the RASSF1A has been detected frequently in the tissues of different cancers [10][11][12][13][14][15][16][17], while in the body fluid, methylation of RASSF1A promoter has also been documented in 50% sputum and 84% serum from lung cancer [30], 35% urine from bladder cancer [15], 56-60% serum from breast caner [31][32][33], and 5% serum from undifferentiated nasopharyngeal carcinoma [34], which indicated the value of RASSF1A methylation in DNA for the early-stage diagnosis of tumors. Detection of methylated DNA has then been suggested as a potential biomarker for early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is no information presently available about the protein status of RASSF1A in liver tissue microarrays (TMAs). Recent studies have also shown that inactivation of RASSF1A promoter by methylation was detectable in tumor cell lines and tissues, such as lung [10], gallbladder [11], breast [12], kidney [13], prostate [14], endometrium [7], bladder [15], bile ducts [16], stomach [17], and colon and rectum carcinoma [17]. The hypermethylation of RASSF1A suggests new perspectives for the diagnosis of malignant tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The RASSF1A (Ras-associated domain family 1) tumor suppressor gene is located on 3 p21.3, the short arm of chromosome 3, which acts as an inhibitor of the cycline D1 protein. Also, it plays a key role as an interactor with the proteins of the retinoblastoma family and negative regulator of cell proliferation through the G1/S inhibitor and mitotic checkpoint (6)(7)(8)(9)(10). Loss of expression of this gene occurs more frequently by hypermethylation that is capable of causing the development of human cancers (10).…”
Section: Introductionmentioning
confidence: 99%